Structural Characterization and Anticomplement Activity of an Acidic Heteropolysaccharide from Lysimachia christinae Hance - Hong, Zhou; Zhou, Li-Shuang; Zhao, Zhi-Zhi; Yuan, Guo-Qi; Wang, Xiao-Jiang; Lu, Yan; Chen, Dao-Feng (Planta Medica, 2023)
A novel acidic heteropolysaccharide (LCP-90-1) was isolated and purified from a traditional “heat-clearing” Chinese medicine, Lysimachia christinae Hance. LCP-90-1 (Mw, 20.65 kDa) was composed of Man, Rha, GlcA, Glc, Gal, and Ara, with relative molar ratios of 1.00: 3.00: 11.62: 1.31: 1.64: 5.24. The backbone consisted of 1,4-α-D-GlcpA, 1,4-α-D-Glcp, 1,4-β-L-Rhap, and 1,3,5-α-L-Araf, with three branches of β-D-Galp-(1 → 4)-β-L-Rhap-(1→, α-L-Araf-(1→ and α-D-Manp-(1→ attached to the C-5 position of 1,3,5-α-L-Araf. LCP-90-1 exhibited potent anticomplement activity (CH50: 135.01 ± 0.68 µg/mL) in vitro, which was significantly enhanced with increased glucuronic acid (GlcA) content in its degradation production (LCP-90-1-A, CH50: 28.26 ± 0.39 µg/mL). However, both LCP-90-1 and LCP90-1-A were inactivated after reduction or complete acid hydrolysis. These observations indicated the important role of GlcA in LCP-90-1 and associated derivatives with respect to anticomplement activity. Similarly, compared with LCP-90-1, the antioxidant activity of LCP-90-1-A was also enhanced. Thus, polysaccharides with a high content of GlcA might be important and effective substances of L. christinae.
Keywords: Primulaceae; Lysimachia christinae; Polysaccharide; structural characterization; anticomplement